AORTIC-BRACHIAL STIFFNESS MISMATCH IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS. (June 2018) - Troitskaya, E.; Starostina, E.; Kobalava, Z.
Abstract : Objective: Aortic stiffness (AS) is a strong predictor of cardiovascular (CV) mortality in various clinical conditions. The impact of AS on CV outcomes is mediated by the reversal of the AS gradient. Its negative prognostic significance has been studied only in the dialysis population. Aim of the study: to assess AS gradient in patients with arterial hypertension (AH) and type 2 diabetes mellitus (T2DM). Design and method: The study group included 90 patients (39% males, mean age 63, 8 ± 11, 6 years, 44% smokers, 80% with dyslipidemia, mean office BP 146 ± 23/86 ± 10 mmHg); control group included 42 patients with AH matched by basic parameters. Median duration of diabetes was 8, 5 years (IQR 2;13). All patients received combined antihypertensive therapy, target BP < 140/85 mmHg was achieved in 29 (52, 7%) patients. BP was measured with a validated oscillometric device. Parameters of arterial stiffness (AS) were assessed by applanation tonometry. AS gradient was calculated as carotid-femoral (cf)PWV/carotid-radial (cr)PWV and its elevation > 1 was considered as AS mismatch. p < 0, 05 was considered significant. Results: Mean cfPWV was 10, 5 ± 2, 4 vs 9, 5 ± 1, 8 m/s (p = 0, 04), crPWV – 8, 5 ± 1, 4 vs 10, 4 ± 1, 7 m/s (p = 0, 001), AS gradient – 1, 2 ± 0, 3 vs 0, 9 ± 0, 1 (p = 0, 04). Incidence of AS mismatch in the study group was 93% vs 19% in the control group (χ2 = 59, 5, p < 0, 001) and 70% vs 9% in the group with PWV < 10 m/s respectively (χ2 = 37, 1, p < 0, 05). Patients with AS gradient > 1, 0 were older (65, 2 ± 10, 7 vs 59, 1 ± 10, 7 years), had longer median duration of DM (10 vs 3 years), higher creatinine (96, 8 ± 21, 1 vs 91, 3 ± 22, 1 μmol/l) and lower GFR (62 ± 18 vs 70 ± 20 ml/min/1, 73m2), p < 0, 05 for trend. Spearmen analysis revealed significant correlations between AS gradient and age (r = 0, 4), DM duration (r = 0, 3), creatinine (r = 0, 2) and GFR (r = −0, 2), p < 0, 05 for trend. Age and DM duration were significant predictors of aortic-brachial stiffness mismatch (β = 0, 4, p = 0, 0002 and β = 0, 3, p = 0, 004, respectively). ROC analysis showed that presence of DM was an early factor of AS mismatch with AUC 0, 849, sensitivity of 98% and specificity of 58%, p < 0, 05. Conclusions: In diabetic patients with arterial hypertension AS mismatch is highly prevalent and in patients with normal PWV may be regarded as an early marker of arteriolosclerosis.